INVESTIGATION OF THE EFFECT OF DEPOSIT LAYER ON HEAT TRANSFER IN THE TRIGA MARK-II NUCLEAR RESEARCH REACTOR COOLING SYSTEM - Akay, Orhan Erdal; Das, Mehmet (Vinca Inst Nuclear Sci, 2022)
In this presented study, the cooling problem of the I.T.U. Triga Mark-II reactor has been handled and analyzed, and solutions were proposed. First of all, a thermal model of the reactor, heat exchanger, and cooling tower trio was established in the reactor. With this model, which was obtained with the help of experimental data, the parameters affecting the change of reactor water temperature over time were determined, and significant findings were obtained by investigating the pos-sibilities of increasing the cooling power of the existing system. Then, using these mathematical equations, the effects of parameters that can affect the power of the reactor cooling system are investigated. The parameters affecting the cooling pow-er are the cooling water flow rates in the second cooling circuits and the depos-ited layer that may exist as a result of numerical calculations. Different models have been created with machine learning algorithms (page regression, decision tree) to estimate the effect of the deposit layer. The mathematical and predictive models obtained with the experimental data for the heat transfer coefficient of the deposit layer, hbd, were compared. The pace regression algorithm modeled the hbd values with the least error rate (RMSE: 1.66) among the models. It has been cal-culated that the average tank water temperature will decrease by approximately 3.5 degrees C if the deposits layer is cleared.
Keywords: Triga Mark-II; heat exchanger; deposit layer; equation derivation; heat transfer coefficient; machine learning algorithm